Craniofacial Morphological Features in Childhood Age with Autism Spectrum Disorder - Çetinkaya, Fatih; Çetinok, Hürriyet (The European Research Journal, 2026)
Objectives: Autism spectrum disorder often exhibits unusual craniofacial morphology, which may indicate underlying neurodevelopmental abnormalities in childhood. This study aimed to investigate the relationship between craniofacial anthropometric measurements, the severity of autism, and language development in children with autism spectrum disorder. Methods: This study included 66 children (50 boys, 16 girls) aged 6–10 years who were diagnosed with autism spectrum disorder. Three-dimensional facial scanning was performed after the removal of glasses, and anthropometric measurements were analyzed in relation to scores on the Gilliam Autism Rating Scale and the Turkish Communication Development Inventory. Results: A significant association was found between increased head circumference and higher autism severity (P=0.035), with larger head size correlating with decreased forehead height, may suggest greater symptom severity in boys. No significant associations were observed in girls. Craniofacial metrics showed no association with language development in either gender. Conclusions: Head circumference and forehead height have been identified as potential craniofacial indicators of autism severity in boys with autism spectrum disorder. These findings highlight the effectiveness of craniofacial phenotyping in clarifying the neurodevelopmental characteristics associated with autism. Future research, utilizing larger and more sex-balanced cohorts, is imperative to clarify these relationships and their potential diagnostic relevance.